Determinants of both classic and skate cross-country ski performance in competitive junior and collegiate skiers - Heil, D. P.; Willis, S. J. (Science and Skiing V. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2012)
INTRODUCTION: Multiple regression analysis is a common analytical tool for describing combinations of physiological, anthropomorphic, and demographic characteristics most strongly associated with successful sports performance. The purpose of the present study was to use this analytical technique to determine the best combination of laboratory lest measures for predicting classic and skate skiing performance in junior and collegiate skiers.